(untitled) (Fiep Bulletin - online, 2011)
The climacteric is understood as the transition between the reproductive and non reproductive womens’ life. It is characterized physiologically by the depletion of ovarian follicles, which may cause morphological changes, functional, hormonal, in target tissues, adversely affecting women’s health. The Family Health Strategy is shown as an important instrument in the care of women in climateric and its proposal meets the National Policy for Integral Attention to Women’s Health. This study sought to analyse the assistance offered to women’s in the climacteric of nurses on Family Health Strategy. This is a exploratory and descriptive study, with qualitative observation. The study subjects were fourteen nurses working on the units of Family Health in Cajazeiras-PB/BRAZIL. The data were collect through by interview half-structured and analyzed using content analysis in their mode of thematic analysis. Was identified the referral of the care with specialists, instructions on sintomatology, alimentation, history, lectures, discussions and answering questions individually or in group, care were offered by some nurses in attention to women in climacteric at the Family Health Strategy, but with a strong deficiency in routine practice. It was found that notions about the climacteric, symptomatology and yet assistance of nurses know ledge are deficient. It was noticed that the study subjects keeps its assistance guided in the model maternal and child, care model still hegemonic in the nursing actions developed in the Family Health Strategy. This compromises the effectiveness of attention at the non-reproductive period. Therefore, it is necessary to the implementation of municipal policies to promote training and awareness regarding the inclusion of nursing routine application on attention to women in climacteric.